(untitled) (Revista Contexto & Educação, 2026)
This article aims to present critical reflections on the entrepreneurial university model, using a case study conducted at a Brazilian federal public university located in the state of Rio Grande do Sul as its empirical foundation. The study seeks to investigate how the incorporation of the entrepreneurial university discourse by this institution reflects the influence of the managerial and corporate model on its institutional practices and organizational structure. The central argument is that, by disseminating this discourse internally, public universities end up reproducing business-oriented practices and values, gradually becoming guided by economic logic and increasingly aligned with market and capital interests. The analysis of data — collected through interviews with university managers, institutional documents, and non-participant observation — reveals that the university under study circulates a series of references associated with the valorization of innovation, closer ties with the productive sector, and academic entrepreneurship, aiming to contribute to economic development. However, it is important to note that this perspective is not unanimous among the institution’s professionals, reflecting ongoing disputes over the meanings attributed to the role of the public university.